2021
DOI: 10.2147/cmar.s299020
|View full text |Cite
|
Sign up to set email alerts
|

A Nomogram Based on CT Deep Learning Signature: A Potential Tool for the Prediction of Overall Survival in Resected Non-Small Cell Lung Cancer Patients

Abstract: To develop and further validate a deep learning signature-based nomogram from computed tomography (CT) images for prediction of the overall survival (OS) in resected non-small cell lung cancer (NSCLC) patients. Patients and Methods: A total of 1792 deep learning features were extracted from nonenhanced and venous-phase CT images for each NSCLC patient in training cohort (n=231). Then, a deep learning signature was built with the least absolute shrinkage and selection operator (LASSO) Cox regression model for O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…It is still a long way to go from nomogram to an artificial intelligent model, but such perspective application would greatly help the diagnosis and prolong patients' life span. The deep learning signature-based nomogram would be a robust tool for the prognostic prediction in the resected NSCLC patients [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is still a long way to go from nomogram to an artificial intelligent model, but such perspective application would greatly help the diagnosis and prolong patients' life span. The deep learning signature-based nomogram would be a robust tool for the prognostic prediction in the resected NSCLC patients [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, native ML models cannot handle time-to-event data while accommodating censored observations. Reflecting this, we found that ML studies predicting NSCLC/LAD survival mainly formulated the survival analysis as a classification problem and transformed time-to-event data into dichotomized endpoints ( 90 94 , 96 , 100 , 102 , 103 , 106 , 108 111 , 113 , 116 , 117 , 134 , 135 ). To this end, utilizing Random Survival Forests (RSF) for continuous time-to-event survival prediction and those aiming to identify optimal time-to-event ML models were emerging ( 98 , 99 , 101 , 105 ), but further applications and research in this area are warranted.…”
Section: Resultsmentioning
confidence: 99%
“…DL, a subset of machine learning, is a new diagnostic technology for mining internal information from medical images. DL can be applied to tumor segmentation [ 20 ], prognosis prediction [ 21 , 22 ], and treatment response evaluation [ 23 ] by automatically extracting deep-learned or high-order image features. Among them, convolutional neural network (CNN) is famous for handling image classification tasks [ 24 ]; the three major operations of CNNs are convolution, activation, and pooling, and the entire process can be divided into two steps: the forward computation and the back propagation [ 25 ].…”
Section: Introductionmentioning
confidence: 99%